Igor Stravinsky - The final chorale - Schönberg, Arnold 1874-1951; Schönberg, Arnold 1874-1951; Schönberg, Arnold 1874-1951; Stravinsky, Igor 1882-1971; Stravinsky, Igor 1882-1971 (Idéale Audience International, 2005)
The Final Chorale tells the story of Igor Stravinsky's Symphonies of Wind Instruments, a piece he composed in 1920 in memory of Claude Debussy. Using for the first time a montage technique juxtaposing short musical sequences and blocks of sound Stravinsky constructed his work as a bold and majestic piece with complex tempo relations which, until today, still strike musicologists, musicians and audiences alike by their originality. Frank Scheffer tells this neo-classical musical adventure in a moving documentary, taking the structure and character of the composition as the basic form for the style and editing of the film. His narration includes an interview with Robert Craft, archival material on Stravinsky and performances by the Netherlands Wind Ensemble conducted by Reinbert de Leeuw. (Covertext) ; en
Enth. außerdem: Arnold Schönberg - Five orchestral pieces. - Produktion: Allegri Film, 1991 (Film 1) und 1994 (Film 2). - Film 1 enthält ausserdem ein Interview mit Robert Craft. - Film 2 befasst sich mit Schönberg's Orchesterstücken, op. 16 (Entstehungsgeschichte, Proben- und Konzertmitschnitte), enthält Aspekte zu Leben und Werk des Komponisten, eine Interpretation des dritten Klavierstückes (aus op. 11), sowie Interviews mit Michael Gielen, Carl Schorske und Charles Rosen. - Interpr.: Charles Rosen, Klavier. Netherlands Radio Philharmonic. Michael Gielen, conductor
12-page booklet inside with authoritative essay, discography and biographies in English, photos
Bonus: Ring, a previously unreleased short feature by Frank Scheffer. Video catalogue. DVD-ROM section with multilingual booklet files
Orig.: 1991
Keywords: Stravinsky, Igor -- 1882-1971; Schönberg, Arnold -- 1874-1951; DVD-Video